Frequency domain MDPSK based non-equalization OFDM for coherent free-space optical communication over modified rician turbulence channel - Chen, Chen (2015)
We apply frequency-domain MDPSK based nonequalization OFDM (NE-OFDM) in coherent FSO communication. Our study shows that NE-OFDM attains a comparable BER performance to equalized OFDM, but with lower complexity and higher spectral efficiency.